Aerosol Optical Depth measurements in the Azores. - Carvalho, Fernanda (2008)
A preliminary analysis of AOD results from sun-photometer measurements collected at Jose Agostinho Observatory at Angra do Heroísmo (Terceira Island, the Azores) was presented. The observational period ranges from August 2004 to December 2007, using a SP02 sun-photometer at wavelengths 412, 500, 675, and 862 nm, coupled to a 2AXP sun-tracker. The sampling interval is 5 s and data is filtered for cloud contamination in a time window of 10 minutes. Most AOD 500 nm values are below 0.3, showing a small variation during the day; frequency distribution shows a typical right skew distribution. Alpha and beta Angstrom coefficients were also computed and analyzed in the same way. Alpha values are generally positive and lower than 4, while beta values are below 1.5. AOD results from the AERONET station at Horta Observatory (Faial Island, the Azores) were also used and compared with Angra data. AOD and Angstrom coefficients were also analyzed with wind results from the automatic weather station located at both observatories. Results show different wind distributions due to different exposures; however, systematic higher AOD values are found at Horta. The proximity of the two sites indicates that these differences are more likely due to different instruments and processing methods used.